Russia Between Two Subcontinents of Eurasia: Advantages and New Threats - Khasbulatov, Ruslan Imranovich (Economy of Regions, 2017)
The geographical location of Russia between Europe and Asia is unique. Russia possesses huge and low-populated territories, which are rich with natural resources. Throughout the centuries, Russia had natural advantages over other countries during the periods of peaceful development as well as during the war years. However, currently, in the conditions of the technological revolution, these advantages may be underestimated. Moreover, these benefits may get under control of Asia or Europe. The country as a geographical region is located between two superpower subcontinental and regional economic centres - the European Union in Europe and China in Asia. These conditions demand, first of all, much more successful development of Russia, or a powerful economic breakthrough. Secondly, the economy of many depressive regions of the country needs an accelerated development. Thirdly, Russia should strengthen its multilateral communications with near neighbours - allies on Eurasian Economic Union to transform this integration group into one of the most successful in the Eurasian region.